Static and free vibration analyses of laminated composite shells by cell-based smoothed discrete shear gap method (CS-DSG3) using three-node triangular elements - Hoa, Pham Quoc; Van, Tran The; Dat, Pham Tien; Hau, Dang Trung; Ha, Nguyen Viet; Hung, Nguyen Manh; Trung, Nguyen Thoi (Vietnam Journal of Mechanics, 2018)
A cell-based smoothed discrete shear gap method (CS-DSG3) using three-node triangular elements was recently proposed to improve the performance of the discrete shear gap method (DSG3) for static and free vibration analyses of isotropic Reissner-Mindlin plates and shells. In this paper, the CS-DSG3 is further extended for static and free vibration analyses of laminated composite shells. In the present method, the first-order shear deformation theory (FSDT) is used in the formulation due to the simplicity and computational efficiency. The accuracy and reliability of the proposed method are verified by comparing its numerical solutions with those of others available numerical results.